2019
DOI: 10.1007/s13762-019-02227-4
|View full text |Cite|
|
Sign up to set email alerts
|

Biochar efficiency in copper removal from Haplic soils

Abstract: The main aim of the study was to examine the biochar efficiency in copper (Cu) ion removal from Haplic (Luvisol, Podzol) soils. In other words, the most effective biochar dose and the most favorable environment pH value were proposed. The copper removal was carried out based on the adsorption process. The results of kinetics measurements were modeled using Richie equation, whereas the adsorption isotherms using Langmuir-Freundlich and Dubinin-Radushkevich equations. The copper removal is a strongly pH-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 74 publications
1
18
0
Order By: Relevance
“…Liang et al (2006) reported that Anthrosols had a (up to 4.8 times) higher surface area than other soils due to their higher biochar concentrations. Similarly, Tomczyk et al (2019) showed that the specific surface area of the nonmodified silty Haplic Luvisol soil is almost three times higher than that of the sandy Haplic Podzol soil; amendment with biochars led to an increase of the specific surface area values in both soils. Modified Haplic Luvisol had a higher surface area due to higher biochar content (approx.…”
Section: Physicochemical Properties Of Soilmentioning
confidence: 89%
See 2 more Smart Citations
“…Liang et al (2006) reported that Anthrosols had a (up to 4.8 times) higher surface area than other soils due to their higher biochar concentrations. Similarly, Tomczyk et al (2019) showed that the specific surface area of the nonmodified silty Haplic Luvisol soil is almost three times higher than that of the sandy Haplic Podzol soil; amendment with biochars led to an increase of the specific surface area values in both soils. Modified Haplic Luvisol had a higher surface area due to higher biochar content (approx.…”
Section: Physicochemical Properties Of Soilmentioning
confidence: 89%
“…These interactions are very specific for biochar, with the exact properties being influenced by feedstock type and pyrolysis conditions (Janus et al 2015;Verheijen et al 2010). Application of biochar can have positive or negative effects on soil properties, including water holding capacity (Revell et al 2012), CEC (Alburquerque et al 2014), bulk density (Cabeza et al 2018), and specific surface area (Tomczyk et al 2019). Data from a few experiments concerning the application of biochar as a soil amendment in different doses on different soil types are presented in Table 3.…”
Section: Biochar Influence On Soil Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, a major challenge for modern agriculture is to reduce soil pollution to improve soil quality. Various soil decontamination techniques have been used to reduce the content of heavy metals (Wuana & Okieimen, 2011), copper (Tomczyk, Boguta, & Sokołowska, 2019), or pesticides (Marican & Durán‐Lara, 2018). One decontamination method proposed is biochar application (Chen et al., 2018; Kavitha et al., 2018; Shaaban et al., 2018; Varjani, Kumar, & Rene, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Houben et al (2012) investigated CaCO 3 , iron grit, fly ash, and bone meal as substances limiting Cd, Zn, and Pb leaching. Tomczyk et al (2019) showed that the biochar obtained from wood wastes effectively binds copper on its surface. Wang et al (2017) performed contaminated soil remediation using various biochars (from pig manure and corn straw) and bacterial strain B. subtilis B38.…”
Section: Introductionmentioning
confidence: 99%